Has cancer survival improved for older people as for younger people? New South Wales, 1980–2012. (August 2018) - Li, Ming; Morrell, Stephen; Creighton, Nicola; Tervonen, Hanna; You, Hui; Roder, David; Currow, David
Highlights: Substantial cancer survival gains occurred over the past three decades in NSW. Survival gains affected a broad cross-section of ages, including older people. The survival of older patients remains lower and their gains have been smaller. The survival gap between older and younger patients has widened. This widening survival gap poses health-service challenges in an aging population. Abstract: Background: Cancer survival has improved markedly in Australia for all ages but it is still lower in older patients. We hypothesize that the survival gap by age has increased. Our rationale is that treatment constraints in older people and potentially their limited participation in trials may have limited opportunities for survival gain. Methods: Post-diagnostic five-year cancer-specific mortality rates were analysed by age group for cancers recorded on the NSW Cancer Registry. Live cases were censored on December 31st, 2012. Hazards ratios (HRs) were obtained from proportional hazards regression for 1990-99 and 2000-12 diagnostic periods, using 1980-89 as the reference, adjusting for socio-demographic factors, degree of cancer spread, and for all cancers combined, for cancer sites. Results: Five-year mortality reduced by diagnostic period for all cancers collectively from 53% in 1980-89 to 33% in 2000-12, with decreases for separate cancer sites. Adjusted HRs (95% confidence intervals) were 0.78 (0.77, 0.80) for 1990-99 and 0.61 (0.58, 0.63) for 2000-12 for all cancers combined. The downward trend in HRs was smaller for the 80+ year age group, leading to significantly higher HRs of 0.83 (0.81, 0.87) and 0.73 (0.70, 0.76) for 1990-99 and 2000-12 respectively. Results were similar using competing risk regression and 5-year rather than 10-year age strata. Conclusion: The reduction in cancer mortality was smaller in older people, as seen in the USA. Research is needed to achieve the best trade-offs between cancer control and harm avoidance in older people. Multidisciplinary teams have an important contribution to make.